The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/qad.0000000000002030
|View full text |Cite
|
Sign up to set email alerts
|

Drug abuse and HIV-related pulmonary hypertension

Abstract: Improved survival among HIV-1 infected individuals with the advent of antiretroviral therapy has clearly led to a greater prevalence of non-infectious complications. One of the most devastating sequelae in these individuals is the development of pulmonary arterial hypertension (PAH). Various epidemiological studies suggest a worse survival of HIV-PAH patients when compared to other forms of PAH. Given that only a subset and not all HIV-infected individuals develop HIV-PAH, suggests that an additional second hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 176 publications
(231 reference statements)
0
14
0
Order By: Relevance
“…11 However, a recent study suggests that pulmonary EC injury alone is insufficient to cause severe PAH, thus highlighting the requirement of additional factors in the development of PAH 12 and importance of a ''double-hit or multiple hits'' mechanism that also applies to PAH animal models. 2,[13][14][15][16] Similar to the injurious effects of SU5416 on pulmonary ECs, morphine has been shown to cause both apoptosis and proliferation of vascular ECs. [17][18][19] We previously reported that the combination of morphine with HIV-infection accentuates pulmonary vascular remodeling characterized by formation of neointimal fibrotic or plexiform lesions in Simian Immunodeficiency Virus (SIV)-infected Rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 However, a recent study suggests that pulmonary EC injury alone is insufficient to cause severe PAH, thus highlighting the requirement of additional factors in the development of PAH 12 and importance of a ''double-hit or multiple hits'' mechanism that also applies to PAH animal models. 2,[13][14][15][16] Similar to the injurious effects of SU5416 on pulmonary ECs, morphine has been shown to cause both apoptosis and proliferation of vascular ECs. [17][18][19] We previously reported that the combination of morphine with HIV-infection accentuates pulmonary vascular remodeling characterized by formation of neointimal fibrotic or plexiform lesions in Simian Immunodeficiency Virus (SIV)-infected Rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%
“…11 However, a recent study suggests that pulmonary EC injury alone is insufficient to cause severe PAH, thus highlighting the requirement of additional factors in the development of PAH 12 and importance of a “double-hit or multiple hits” mechanism that also applies to PAH animal models. 2,1316…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary arterial hypertension (PAH) is one of the most devastating non-infectious complications related to HIV infection and echocardiographic evidences suggest prevalence of increased pulmonary artery systolic pressure (PASP) in 2.6-15.5% of people living with HIV (PLWH) (1), (2). HIV-associated PAH falls under Group I pulmonary hypertension (PH) and the risk factors such as cocaine, methamphetamine and intravenous drug use (IVDU) in PLWH can potentiate the development of HIV-PAH (2)(3)(4). Furthermore, with the increasing burden of cardiac and chronic respiratory complications in PLWH, the prevalence of secondary PH is suggested to increase as well, in these individuals (5,6).…”
Section: Introductionmentioning
confidence: 99%